Course of mental distress among psychotherapists throughout two years of the COVID- 19 pandemic: individual and inter-relational resources make a difference—cross-sectional and longitudinal results of the VOICE study - Mogwitz, Sabine; Wintermann, Gloria Beatrice; Albus, Christian; Baranowski, Andreas M.; Beschoner, Petra; Erim, Yesim; Geiser, Franziska; Jerg-Bretzke, Lucia; Morawa, Eva; Steudte-Schmiedgen, Susann; Weidner, Kerstin (BMC Psychiatry, 2025)
Background: The COVID-19 pandemic has posed challenges to healthcare systems worldwide. For healthcare workers (HCW), an increased prevalence of mental distress and the impact of various resources have been identified. Psychotherapists specialise in helping people cope with stressful life events. At the same time, they are susceptible to mental distress, resulting from their work. Data on symptoms of depression and the role of resources during the COVID-19 pandemic are scarce for psychotherapists. Therefore, the present study aimed to evaluate the course of self-reported depression of psychotherapists throughout the COVID-19 pandemic. Additionally, the impact of resources on depression was evaluated. Methods: We investigated symptoms of depression using the Patient Health Questionnaire-2 (PHQ-2) at four time points (T1-T4) during the COVID-19 pandemic in Germany. The PHQ-2 scores and resources such as sense of coherence (SOC), general optimism and social support (ESSI-D) of the psychotherapists (N = 1733) were compared with those of a comparison sample of HCW (N = 8470). The impact of resources on PHQ-2 scores was examined using cross-sectional linear modelling and longitudinal linear mixed modelling with interactions and lagged predictors. Results: At T1-T4, psychotherapists showed lower mean PHQ-2 scores than the comparison sample (p < 0.001). Among psychotherapists, the PHQ-2 scores increased (T1-T2, and T1-T4, p < 0.050). Cross-sectionally, higher SOC was associated with lower PHQ-2 scores (p < 0.001), with the protective influence weakening over time (p = 0.033). Longitudinal analyses confirmed a protective effect of sense of coherence (stable over time) and general optimism (declining over time) on PHQ-2 scores. An exploratory lagged-predictor analysis suggested that higher social support was associated with lower PHQ-2 scores, whereas higher general optimism was linked to increasing PHQ-2 scores. Conclusions: This study revealed lower levels of depression among psychotherapists compared with the comparison sample throughout the pandemic. Concurrently, the resource levels were mostly comparable and stable, with a protective impact of the sense of coherence (stable) and optimism (decreasing) and an association of high social support with low depression throughout the pandemic. Strengthening the sense of coherence and social support should be the focus of professional and policy attention to improve the ability of psychotherapists to cope with future crises.
CRIS-Team Scopus Importer:2025-05-16
Keywords: COVID- 19; Depression; HCW; Health care workers; Mental distress; Mental health; PHQ- 2; Psychologists; Psychotherapists; Resources; Therapists; Work-related risks